Synthesis, Anticancer Evaluation and Molecular Docking studies of Novel Benzophenone based 1,2,3-Triazole Hybrids - Venkateswara Rao Battula; Swamy Sekhar Kaladi; Leela Prasad Yandrati; Praveen Kumar Edigi; Sushmitha Bujji; Venkatarathnam Nasipireddy; Padma Mogili (Journal of Chemistry Letters)
A series of novel benzophenone based1,2,3-triazole hybrids (8a-l) were synthesized. The biological screening of these compounds was performed on antibacterial, antioxidant, and cytotoxic activity (HT-1080, A-549 cell lines).Compounds 8d, 8h, and 8l are proven to be potent inhibitors against bacterial strains compared to standard drug ampicillin. The cytotoxicity of compounds 8d, 8h, and 8l exhibited promising activity with the best IC50 values comparable to that of standard doxorubicin against HT-1080 and A-549 cell lines. Compounds 8land 8d are highly potent to show the hydrogen donating free radical when compared to the standard Ascorbic acidin the antioxidant study. Molecular docking studies performed between newly synthesized compounds 8a-land target molecules PBP6 of E.coli and ERK2 scored the best binding affinity values and demonstrated binding interactions such as H-bond and hydrophobic.